Positron Emission Tomography Imaging Using Radiolabeled Inorganic Nanomaterials - Sun, Xiaolian (Acc Chem Res, 2015)
Positron emission tomography (PET) is a radionuclide imaging technology that plays an important role in preclinical and clinical research. With administration of a small amount of radiotracer, PET imaging can provide a noninvasive, highly sensitive, and quantitative readout of its organ/tissue targeting efficiency and pharmacokinetics. Various radiotracers have been designed to target specific molecular events. Compared with antibodies, proteins, peptides, and other biologically relevant molecules, nanoparticles represent a new frontier in molecular imaging probe design, enabling the attachment of different imaging modalities, targeting ligands, and therapeutic payloads in a single vector. [Image: see text] We introduce the radiolabeled nanoparticle platforms that we and others have developed. Due to the fundamental differences in the various nanoparticles and radioisotopes, most radiolabeling methods are designed case-by-case. We focus on some general rules about selecting appropriate isotopes for given types of nanoparticles, as well as adjusting the labeling strategies according to specific applications. We classified these radiolabeling methods into four categories: (1) complexation reaction of radiometal ions with chelators via coordination chemistry; (2) direct bombardment of nanoparticles via hadronic projectiles; (3) synthesis of nanoparticles using a mixture of radioactive and nonradioactive precursors; (4) chelator-free postsynthetic radiolabeling. Method 1 is generally applicable to different nanomaterials as long as the surface chemistry is well-designed. However, the addition of chelators brings concerns of possible changes to the physicochemical properties of nanomaterials and detachment of the radiometal. Methods 2 and 3 have improved radiochemical stability. The applications are, however, limited by the possible damage to the nanocomponent caused by the proton beams (method 2) and harsh synthetic conditions (method 3). Method 4 is still in its infancy. Although being fast and specific, only a few combinations of isotopes and nanoparticles have been explored. Since the applications of radiolabeled nanoparticles are based on the premise that the radioisotopes are stably attached to the nanomaterials, stability (colloidal and radiochemical) assessment of radiolabeled nanoparticles is also highlighted. Despite the fact that thousands of nanomaterials have been developed for clinical research, only very few have moved to humans. One major reason is the lack of understanding of the biological behavior of nanomaterials. We discuss specific examples of using PET imaging to monitor the in vivo fate of radiolabeled nanoparticles, emphasizing the importance of labeling strategies and caution in interpreting PET data. Design considerations for radiolabeled nanoplatforms for multimodal molecular imaging are also illustrated, with a focus on strategies to combine the strengths of different imaging modalities and to prolong the circulation time.